2019
DOI: 10.29245/2578-3025/2019/4.1171
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Health Outcomes Following Coronary Artery Bypass Grafting: A Different Journey for Men and Women

Abstract: Background:The applicability of the Short Form (SF36) questionnaire to disparate populations led us to use this tool to investigate how health-related quality-of-life (HRQoL) for patients who underwent coronary artery bypass grafting (CABG) is related to gender, age and survival.Method: SF36 data and the presence of cardiac symptoms were collected from 44 women and 166 men prior to surgery and from consenting survivors at one and eight-year follow-ups. Survival data were collected from government records for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…In this study the rates of recurrence/relief of risks are estimated from data collected at the one and eight-year follow-ups. In this same cohort of patients earlier follow-up showed that well-being (SF36 scores) had also declined despite overall improvements in the initial years after operation 35 . This trend has been reported in other larger researches.…”
Section: Discussion Of Resultsmentioning
confidence: 79%
“…In this study the rates of recurrence/relief of risks are estimated from data collected at the one and eight-year follow-ups. In this same cohort of patients earlier follow-up showed that well-being (SF36 scores) had also declined despite overall improvements in the initial years after operation 35 . This trend has been reported in other larger researches.…”
Section: Discussion Of Resultsmentioning
confidence: 79%